Age and Gender Wise Prevalence Of Dental Caries Among Children - A Retrospective Analysis - FATHIMA, HENA MARIAM; RAMAKRISHNAN, MAHESH (The journal of contemporary issues in business and government, 2021)
Dental caries is a chronic disease with multifactorial etiology, with variable pathogenesis and is the most prevalent unmet health care need in children. The aim of the study is to evaluate the age and gender wise prevalence of dental caries among children. A retrospective study was carried out among children reported to a private Dental University from June 2019-March 2020. Patient records were collected and evaluated independently by calibrated examiners. Patients in the age group of 6-16 years were selected for the study. A total of 217 patients met the inclusion criteria and were eligible for the study.The mean DMFT/dmft score was found to be 3.78. Chi square analysis showed no statistically significant result between gender and DMFT/dmft score, since p value >0.05. Males were more affected than females. It can be concluded that caries prevalence and mean DMFT/dmft was found to be higher in males and in the age group of 6-8 years specifically.